Congenital Chloride Diarrhea: Diagnosis by Easy-Accessible Chloride Measurement in Feces - C. Gils; M.-C. Eckhardt; P. E. Nielsen; M. Nybo (Case Reports in Pediatrics)
Background. Congenital chloride diarrhea (CCD) is an autosomal recessive disorder caused by mutations in the genes encoding the intestinal Cl−/HCO3- exchanger and is clinically characterized by watery, profound diarrhea, electrolyte disturbances, and metabolic alkalosis. The CCD diagnosis is based on the clinical symptoms and measurement of high chloride concentration in feces (>90 mmol/L) and is confirmed by DNA testing. Untreated CCD is lethal, while long-term clinical outcome improves when treated correctly. Case Presentation. A 27-year-old woman had an emergency caesarian due to pain and discomfort in gestational week 36 + 4. The newborn boy had abdominal distension and yellow fluid per rectum. Therapy with intravenous glucose and sodium chloride decreased his stool frequency and improved his clinical condition. A suspicion of congenital chloride diarrhea was strongly supported using blood gas analyzer to measure an increased chloride concentration in the feces; the diagnosis was confirmed by DNA testing. Discussion. Measurement of chloride in feces using an ordinary blood gas analyzer can serve as a preliminary analysis when congenital chloride diarrhea is suspected. This measurement can be easily performed with a watery feces composition. An easy-accessible chloride measurement available will facilitate the diagnostics and support the initial treatment if CCD is suspected.